Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward & Peppard: (Studi Kasus: CV Prima Puspasari) - Evelinda Marsya Asterina; Anandita Norma Kusuma Maharani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The digital transformation era demands printing companies to strategically integrate information technology to enhance efficiency and competitiveness. CV Prima Puspasari still faces several challenges in business process management, such as unintegrated workflows, manual record-keeping, and limited utilization of information systems. This study aims to develop an Information Systems Strategic Planning (ISSP) using the Ward & Peppard method as the main analytical framework. The approach analyzes business and technology conditions through four domains: internal and external business environments, as well as internal and external IS/IT environments. The analysis combines SWOT Analysis, Value Chain Analysis, and the McFarlan Strategic Grid to identify strengths, weaknesses, opportunities, threats, and to determine application priorities. The results produce three main strategies: IS/IT business strategy, IS/IT management strategy, and IT infrastructure strategy. The recommended systems include Inventory Management System, Customer Relationship Management (CRM), Integrated Financial System, Human Resource Information System (HRIS), E-Procurement, and E-Commerce. This strategic planning is expected to serve as a roadmap for CV Prima Puspasari in implementing digital transformation, improving operational effectiveness, and strengthening its competitive advantage in the digital printing industry.